Synthesis, Crystal Structure, Anti-inflammatory and Anti-hyperglycemic Activities of Novel 3,4-Disubstituted 1,2,4-Triazol-5(4H)-one Derivatives - Saleem, Muhammad; Yu, Seon-Mi; Rafiq, Muhammad; Kim, Song-Ja; Seo, Sung-Yum; Hwan Lee, Ki (Medicinal Chemistry, 2014)
A new series of 3,4-disubstituted 1,2,4-triazol-5(4H)-one 5a-r, bearing various methoxyphenyl, fluorophenyl, tolyl and phenyl groups, was synthesized by the dehydrocyclization of hydrazinecarboxamides 4a-r by refluxing in a 2 N sodium hydroxide solution. Hydrazinecarboxamides 4a-r was synthesized via the condensation of the corresponding aralkanoic acid hydrazides, 3a-g, with fluoro-, tolyl- and methoxyphenylisocyanates. The newly synthesized compounds (5ar) were characterized by IR, 1H NMR and 13C NMR analyses. The structure of one compound 5a was determined by single crystal X-ray diffraction analysis. All of the synthesized compounds were screened for their anti-inflammatory and anti-diabetic (α-glucosidase and α-amylase inhibition) activity to identify new drugs that might be useful in preventing damage related to diabetes and inflammation. Compounds 5j, 5k and 5m decrease the expression of type II collagen in a dose dependent manner; similarly 5l decrease the COX-2 expression of rabbit articular chondrocytes in a dose dependent manner possessing potent anti-inflammatory potential while some of derivatives including 5c, 5e, 5g and 5h cause inflammation. Meanwhile, excellent α-glucosidase and moderate α-amylase inhibitory profiles against carbohydrate modulating enzymes were demonstrated by compounds 5b, 5f, 5k and 5q compared to the reference standard acarbose, and compounds 5g, 5h, 5i, 5j, 5l and 5o exhibited moderate to low enzyme inhibition potential among the series.
Keywords: collagen type II